RANCANGAN SISTEM PENANGANAN MATERIAL UNTUK MEMINIMASI RISIKO GANGGUAN SISTEM TULANG DAN OTOT - Yanti Helianty; Dinni Emalia; Caecilia Sw (Teknoin, 2016)
Manual Material Handling process often caused a danger to the health and safety workers, such as accidents at work and injured muscle (musculoskeletal disorder) on the part of worker’s body. In this study will suggest to improve the alternative of manual handling in Menjangan soy sauce factory. From di proposed result that the work force on segment of the worker’s body smaller than the work force by using the old way. With a smaller force, the moment that occurs will be samller, so that the work load becomes lighter. With a lighter work load can minimize the possibility of a muscle injury in the works.